2024
DOI: 10.23736/s1973-9087.24.08087-0
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in functional connectivity in patients with non-specific chronic low back pain after motor control exercise: a randomized trial

Chanjuan ZHANG,
Zhou ZHANG,
Yuelong LI
et al.

Abstract: BACKGROUND Motor control exercise (MCE) is effective in alleviating non-specific chronic low back pain (NCLBP). Neuro-imaging research is warranted to explore the underlying neural mechanisms of MCE. AIM We used resting-state functional magnetic resonance imaging (rs-fMRI) to explore the central mechanism underpinning the effects of MCE in patients with NCLBP. DESIGN A randomized, single-blinded, controlled trial. SETTING … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
0
0
Order By: Relevance
“… 32 Another study reported significantly altered EC in the cerebellum-neocortex and cerebellum-basal ganglia circuits in patients with major depressive disorder, 31 and decreased rsFC between bilateral cerebellar and cortical brain regions in patients with cLBP after motor control exercise. 62 Both the brainstem and the cerebellum have important roles in the regulation of pain and emotion; therefore, the abnormalities of the rsFC and EC between them and NAC may be an important reason for the persistence of pain and negative emotions in cLBP.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Another study reported significantly altered EC in the cerebellum-neocortex and cerebellum-basal ganglia circuits in patients with major depressive disorder, 31 and decreased rsFC between bilateral cerebellar and cortical brain regions in patients with cLBP after motor control exercise. 62 Both the brainstem and the cerebellum have important roles in the regulation of pain and emotion; therefore, the abnormalities of the rsFC and EC between them and NAC may be an important reason for the persistence of pain and negative emotions in cLBP.…”
Section: Discussionmentioning
confidence: 99%